APPLICATION OF CELLULAR AUTOMATA IN THE SPREAD OF FOREST AND LAND FOREST, CASE STUDI: CENTRAL KALIMANTAN AND SURROUNDING AREA. - Umma Zahra, Usnida
Cellular automata is a method that can simulate the spread of fires in forests or land. The spread of fire occurs when there is land that is burned and surrounded by areas that are prone to burning. The speed of the spread of fire depends on the condition of the land, ranging from wind conditions, topography, and land cover, so that some land is quickly anchored by fire, some are slow. Fire resistance in the event of a fire is due to the presence of heat, oxygen, and fuel. This is also related to the amount of carbon content in land cover. The more carbon it contains, usually the land that is on fire will be more difficult to extinguish. In this study, a forest and land fire distribution model is constructed by observing the speed of extinguishment using cellular automata. Central Kalimantan and surrounding areas are chosen as the model dataset. Central Kalimantan is one of the areas that often experiences forest and land fires. Based on the results of fire spread simulations conducted for 3 days with 265 hotspots, it is estimated that there are 3.231, 7 km2 of burned land area. Changes in wind conditions and land cover also contribute to the spread of forest and land fires.